2013
DOI: 10.7567/jjap.52.110125
|View full text |Cite
|
Sign up to set email alerts
|

Control of Surface Work Function by Depositing Insulating Oxide Capping Layers

Abstract: We have studied the work function modulation in pulsed laser deposited nonpolar MgO (100) and polar MgO (100) and LaAlO3 (100) insulating oxide films on Nb:SrTiO3 (100) and (111) substrates using Kelvin probe measurements. The work function modulation in MgO/Nb:SrTiO3 is ∼1 eV, which may be understood by the “electron compression model”, where the leaked-out electrons from Nb:SrTiO3 surface are pushed back by MgO layer, reducing the surface dipole moment. By forming double insulating top layer in LaAlO3/nondop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Thus, we obtain ϕ (STO) = 4.5 eV, ϕ (20uc-FeSe/STO) = 5.1 eV and ϕ (1uc-FeSe/STO) = 4.8–5.2 eV, as summarized in Figure 2b . The obtained work function of STO is consistent with previous reports 35 . When FeSe is deposited onto STO, electrons in STO transfer to FeSe to compensate for the large difference in work functions.…”
Section: Resultssupporting
confidence: 92%
“…Thus, we obtain ϕ (STO) = 4.5 eV, ϕ (20uc-FeSe/STO) = 5.1 eV and ϕ (1uc-FeSe/STO) = 4.8–5.2 eV, as summarized in Figure 2b . The obtained work function of STO is consistent with previous reports 35 . When FeSe is deposited onto STO, electrons in STO transfer to FeSe to compensate for the large difference in work functions.…”
Section: Resultssupporting
confidence: 92%
“…[22][23][24] Such advances are key to studying the work function of complex materials, which is sensitive to growth parameters and conditions. Whereas some studies have reported work function values for several of these materials, [25][26][27][28] the literature concerning specifically tailored work functions of perovskite oxide heterostructures is rather scarce. [10,21,29] A particularly interesting application motivating this work is that of thermoelectronic energy converters (TECs), [30] which utilize a hot thermionically emitting material and the condensation of electrons on a cold collecting material.…”
Section: Introductionmentioning
confidence: 99%